STRATEGI KOORDINASI BAPPELITBANG KOTA BANDUNG DALAM PENYUSUNAN PERUBAHAN RPJMD KOTA BANDUNG - Salwa Rizki Aulia; Muhamad Nur Afandi (Politeknik STIA LAN Bandung, 2022)
Processes and mechanisms that are too long in the preparation of development planning documents often lead to inappropriate completion. This is a challenge for the Development Planning, Research and Development Agency of Bandung City as a technical institution that manages development planning in Bandung City. This study aims to overcome obstacles related to coordination during the preparation of planning documents and to propose the formulation of a coordination strategy in the preparation of changes to the Regional Medium Term Development Plan (RPJMD). This research was conducted using a case study method by combining qualitative and quantitative methods (mix methods). Data analysis was performed using SWOT analysis. Data were obtained through observation, document studies, and interviews. The results of this study illustrate that there is still a lack of synchronization of understanding and action regarding the flow of mechanisms that will be taken by the parties involved. This shows that the coordination strategy used by the Development Planning, Research and Development Agency of Bandung City has not been optimal, causing delays in the completion of changes to the RPJMD. Strategy development and renewal is one of the efforts to overcome these obstacles